2013
DOI: 10.1177/2051415813493417
|View full text |Cite
|
Sign up to set email alerts
|

The new standard of care in urology outpatients? A one-stop clinic improves efficiency and quality

Abstract: Objective The objective of this article is to determine retrospectively if a one-stop clinic for all new urology referrals improved the efficiency and quality of our outpatient pathway. We considered any improvement in productivity (e.g. waiting times) to indicate improved efficiency as resources were not increased. We considered any improvement in the level and continuity of specialist care to indicate improved quality as these factors have both been associated with measures of quality such as patient satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…there were no clinics that accepted referrals where there was a general suspicion of cancer. The indications for referral included: seven studies on post-menopausal or abnormal vaginal bleeding (20)(21)(22)(23)(24)(25)(26), six studies on breast symptoms (14,15,(27)(28)(29)(30), three for lower gastrointestinal (GI) symptoms (16,31,32), three for elevated prostate specific antigen (PSA) (17,18,33), three for testicular symptoms (34)(35)(36), two for urological symptoms (37,38), two for dyspepsia (39,40), one for haematuria (19), one for unexplained lymphadenopathy (41), and one for neck lumps (6). When reported, one-stop clinics were held in a hospital setting.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…there were no clinics that accepted referrals where there was a general suspicion of cancer. The indications for referral included: seven studies on post-menopausal or abnormal vaginal bleeding (20)(21)(22)(23)(24)(25)(26), six studies on breast symptoms (14,15,(27)(28)(29)(30), three for lower gastrointestinal (GI) symptoms (16,31,32), three for elevated prostate specific antigen (PSA) (17,18,33), three for testicular symptoms (34)(35)(36), two for urological symptoms (37,38), two for dyspepsia (39,40), one for haematuria (19), one for unexplained lymphadenopathy (41), and one for neck lumps (6). When reported, one-stop clinics were held in a hospital setting.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the findings of this review, we are unable to comment on the risk of overdiagnosis in one-stop clinics: only one study reported patients diagnosed with asymptomatic breast cancer and most also had symptomatic breast cancer (29). Some authors considered the CR's for cancer and serious disease to be too low (30,39) whilst others concluded that testing more patients to reduce the risk of under-diagnosis was important (19,37). GPs will play a vital role in minimising inappropriate referrals to achieve a balance between under-and overdiagnosis.…”
Section: Implications For Research and Practicementioning
confidence: 98%
See 3 more Smart Citations